Novel mercerized Haloxylon salicornicum Sahara plants derived adsorbents for efficient removal of lead(II) from wastewater - Magda A. Akl; Asmaa A. Serage; Aya G. Mostafa; Yasser A. El-Amier (Scientific Reports)
Abstract In an effort to valorize the use of Egyptian Sahara plants as biomaterials for the heavy metals remediation from water, we present here a thorough investigation of the utilization of the locally accessible Haloxylon salicornicum (HS) Sahara plant as an adsorbent for Pb(II) remediation. The raw HS and the mercerized one (HSN) adsorbents were characterized by Boehm’s titration method, Fourier Transform infra-red (FTIR), scanning electron microscopy (SEM), Thermo-gravimetric analysis (TGA), and the pHPZC. Many experimental parameters that influence the Pb(II) adsorption onto these adsorbents were thoroughly studied, such as pH, adsorbent (HS and HSN) dose, initial concentration of metal ion, time of contact, and effect of various foreign ions. Due to the higher R2 values and the lower values of error functions, the adsorption of Pb(II) onto HS and HSN adsorbents was best described by pseudo-2nd-order and Langmuir isotherm model with adsorption capacities of 100.68 and 113.33 mg/g for HS and HSN, respectively. Thermodynamic studies revealed the spontaneous and endothermic nature of the adsorption of Pb(II). The mechanism of the adsorption of Pb(II) onto HS and HSN adsorbents was elucidated.